Magnetic fields as a tool to control superconducting devices - Chaves, Davi Araujo Dalbuquerque (2023)
The quantum nature and dissipation-free flow of electric currents in superconducting materials have taken a central role as technological developments push forward the necessity of new methods for processing and dealing with the amount of information generated by modern consumption patterns. To enable such superconducting technologies, it is necessary to understand the underlying Physics dictating the behavior of superconductors, unveiling or allowing to control phenomena useful for applications. Due to its intrinsic relationship with the superconducting state, applied magnetic fields emerge as natural candidates for manipulating the properties of superconducting materials. These ideas motivated the research conducted in the context of this thesis, which is structured as a collection of studies in which different superconducting systems are subjected to magnetic fields, aiming to investigate and control their behavior. In the first set of results presented, the temperature of a plain Nb thin film is reduced under different magnetic field cooling conditions. Then, flux penetration patterns are studied by magneto-optical imaging (MOI). The results demonstrate how the applied field spatial distribution and direction influence the ability of a superconducting device to transport electrical currents without dissipation, without the need for any complex nanofabrication steps. Such influence is due to the emergence of different trapped flux configurations in the superconductor, either facilitating or hampering further magnetic flux penetration, effectively reducing or increasing the effective maximum current the film can carry in the superconducting state. It is true, however, that for most applications in superconducting technology, nanofabrication is required, in some cases demanding the creation of regions of suppressed superconductivity called weak-links. A different study investigates normal and superconducting state properties of Nb films patterned with a single weak-link fabricated by focused ion beam (FIB) milling. The investigation quantifies the suppression of superconducting properties and the modification of the normal flow of electrons, finding that these are linked by the degree of impurities introduced by the nanofabrication. One interesting effect is the emergence of a local peak in the magnetic field-dependent magnetization of the patterned samples. In a separate work, we employ MOI to investigate these specimens under applied fields near such local peak. This study reveals that the patterned films undergo a behavior transformation from a weak-link to a strong-link, enabling more current to flow between the unpatterned Nb regions. Quantifying the MOI data allows us to understand the flux dynamics responsible for the peak effect. In a different study, the properties of a dc superconducting quantum interference device (SQUID) presenting two parallel weak-links comprised of asymmetric constrictions of a superconducting amorphous MoGe film were investigated. It is possible to influence the behavior of such devices by modifying their geometry. The study demonstrates how understanding the relationship between the device and applied magnetic fields and currents allows preparing the SQUID in multiple energy states, readable at the same field value, thus allowing its use as a multilevel memory element. Finally, we aim to consolidate MOI as a reliable tool to quantitatively study the behavior of superconducting films under ac magnetic fields. For that, we investigate the independence of the thermomagnetic history on the ac magnetic susceptibility response of an amorphous MoSi film. This study relies on the possibility of emulating ac effects by cycling an applied dc field. The results are successfully compared with standard SQUID-based magnetometry while taking advantage of the local spatial resolution of MOI to reveal the quantitative behavior of individual flux avalanche events and the presence of zones of flux annihilation at interfaces between positive and negative flux regions.